2022
DOI: 10.20517/mtod.2022.20
|View full text |Cite
|
Sign up to set email alerts
|

Concise review: gamma-glutamyl transferase - evolution from an indiscriminate liver test to a biomarker of cardiometabolic risk

Abstract: This concise review article critically examines the recent medical literature regarding gamma glutamyl transferase (GGT) with a special emphasis on newly proposed indications for GGT use, including cardiovascular risk assessment. GGT is a ubiquitous glycosylated protein embedded in the outer surface of cell membranes, which catalyzes the transfer of glutamyl groups from various substrates and plays a key role in the antioxidant/pro-oxidant balance. In the past, the enzyme was considered a non-specific liver t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Current evidence indicates that MAFLD and CKD are two risk factors for adverse cardiovascular outcomes and all-cause mortality ( 106 - 109 ). Increasing evidence recommends that patients with MAFLD should be treated early and aggressively for obesity and other coexisting cardiometabolic risk factors ( 110 , 111 ). Most available drugs that target cardiometabolic risk factors exert their actions either directly or indirectly on glucose and lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence indicates that MAFLD and CKD are two risk factors for adverse cardiovascular outcomes and all-cause mortality ( 106 - 109 ). Increasing evidence recommends that patients with MAFLD should be treated early and aggressively for obesity and other coexisting cardiometabolic risk factors ( 110 , 111 ). Most available drugs that target cardiometabolic risk factors exert their actions either directly or indirectly on glucose and lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…However, multiple population‐based studies suggest that GGT is an independent risk factor for SLD, and that increased GGT levels may be associated with the severity of steatosis and fibrosis 14,15 . Elevated GGT has also been suggested to predict the development of portal hypertension in cardiometabolic disease in the general population 16–18 . It is hypothesized that GGT elevation is not just due to release from injured cells in the setting of chronic liver disease, but also accelerated synthesis of GGT and/or release of GGT into the bloodstream 16–18 .…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Elevated GGT has also been suggested to predict the development of portal hypertension in cardiometabolic disease in the general population. [16][17][18] It is hypothesized that GGT elevation is not just due to release from injured cells in the setting of chronic liver disease, but also accelerated synthesis of GGT and/or release of GGT into the bloodstream. [16][17][18] GGT has low specificity, and its role in TS will need continued study, but our results suggest that it may assist in SLD risk assessment in TS.…”
Section: Ta B L E 3 Summary Statistics Between Ts Patients and Controlsmentioning
confidence: 99%
“…Several studies have reported a reciprocal comparison of the prediction efficacy of FLI, HSI, FSI, and ZJU index [16,18,44]. Obviously, the algorithms and equations differ from each other.…”
Section: Discussionmentioning
confidence: 99%